Identification and Functional Characterization of Divergent 3’-Phosphate tRNA Ligase From Entamoeba histolytica - Peng, Ruofan; Yoshinari, Shigeo; Kawano-Sugaya, Tetsuro; Jeelani, Ghulam; Nozaki, Tomoyoshi (Frontiers in Cellular and Infection Microbiology, 2021)
HSPC117/RtcB, 3’-phosphate tRNA ligase, is a critical enzyme involved in tRNA splicing and maturation. HSPC117/RtcB is also involved in mRNA splicing of some protein coding genes including XBP-1. Entamoeba histolytica, a protozoan parasite responsible for human amebiasis, possesses two RtcB proteins (EhRtcB1 and 2), but their biological functions remain unknown. Both RtcBs show kinship with mammalian/archaeal type and all amino acid residues present in the active site are highly conserved, as suggested by protein alignment and phylogenetic analyses. EhRtcB1 was demonstrated to be localized to the nucleus while EhRtcB2 was in the cytosol. EhRtcB1, but not EhRtcB2, was required for optimal growth of E. histolytica trophozoites. Both EhRtcB1 and EhRtcB2 showed RNA ligation activity in vitro. The predominant role of EhRtcB1 in tRNAIle (UAU) processing in vivo was demonstrated in EhRtcB1- and 2-gene silenced strains. Taken together, we have demonstrated conservation of tRNA splicing and functional diversification of RtcBs in this amoebozoan lineage.